Associated resistance of Escherichia coli isolated from humans and animals to polymyxin and beta-lactam antibiotics - O. S. Sulian; V. A. Ageevets; A. A. Sukhinin; I. V. Ageevets; S. R. Abgaryan; S. A. Makavchik; O. A. Kameneva; K. G. Kosyakova; T. M. Mrugova; D. A. Popov; O. E. Punchenko; S. V. Sidorenko (Антибиотики и Химиотерапия)
Escherichia coli isolates from various sources from 2018 to 2019 were included in the study. Mcr-1 genes were found in two of 105 animal strains (2%) and seven of 928 human strains (0.8%). All mcr-1-positive strains showed a low level of resistance to colistin (MIC ranged from 4 to 8 µg/ml). Both strains isolated from animals remained sensitive to betalactam antibiotics and did not contain beta-lactamase genes. Beta-lactamases were absent only in one of the strains isolated from humans. Four strains were resistant to cephalosporins with sensitivity to carbapenems and carried class A (blaCTX-M-15 or blaCTX-M-1) or class C (blaCMY-2) extended-spectrum beta-lactamases genes. One strain showed resistance to cephalosporins and meropenem and contained four beta-lactamase genes: blaNDM-1, blaCTX-M-15, blaTEM-1B, and blaCMY-6. Only one strain isolated from animals remained sensitive to ciprofloxacin, the rest showed high level of resistance, had amino acid substitutions in the DNA gyrase genes or mutations leading to overexpression of the mdfA gene. In terms of resistance to aminoglycosides, the strains varied widely and carried up to four aminoglycoside-modifying enzyme genes. One strain isolated from humans showed resistance to tigecycline, but no genes conferring resistance to this antibiotic were found. The data obtained substantiate the need for extended studies on the molecular epidemiology of associated resistance to polymyxins and beta-lactams.